Improved cycling performance and rate stability of ITO-compounded Li2MnSiO4 for lithium-ion batteries. Issue 18 (12th March 2018) - Liu, Jingya; Li, Yonghu; Yang, Shuai; Ai, Jinjin; Lai, Chunyan; Xu, Qunjie
Abstract : Li2 MnSiO4 compounded with indium tin oxide (ITO) was successfully synthesized through a sol–gel method. Abstract : Li2 MnSiO4 compounded with indium tin oxide (ITO) was successfully synthesized through a sol–gel method. The structure and morphology characterization of Li2 MnSiO4 /ITO nanocomposite are demonstrated by XRD, SEM, TEM, EDS and XPS. Galvanostatic charge–discharge tests, EIS and CV are employed to examine the electrochemical performance of the composite. From those results, it could be observed that the electrochemical performance of Li2 MnSiO4 cathode material has been significantly improved due to the introducing of indium tin oxide. The 3 wt% ITO-compounded sample displayed a discharge specific capacity around 141 mA h g −1 at 0.05C, 134.4 mA h g −1 at 0.1C, 132.9 mA h g −1 at 0.2C and 127.4 mA h g −1 at 0.5C in the first cycle, which is much higher than the pristine sample.